PENGEMBANGAN PERANGKAT PEMBELAJARAN BIOLOGI SMP RSBI BERORIENTASI PENDEKATAN RECIPROCAL TEACHING PADA MATERI SISTEM PERNAPASAN MANUSIA - Arfiane, Chusnul; Kardi, Soeparman; Yuanita, Leny (JPPS (Jurnal Penelitian Pendidikan Sains), 2011)
The objectives of this research were: 1) to develop appropriate biology instruction materials for the pilot international standard junior high school students, and  2)  to describe the implementation results of the developed biology instruction materials for the pilot international standard junior high school students.  Instructional materials consisted of the lesson plans, the student’s worksheet, the student’s book and the achievement test were developed by implementing reciprocal teaching approach. Research subject for the first implementation of  the developed biology instruction materials was twelve students and the second implementation was  twenty-three students of The Pilot International Standard Junior High School 1 Ngoro Mojokerto. Research Design for the implementation was one group pretest-postest design. The instructional materials had been validated and the results showed that  the instructional materials were appropriate to be implemented.  Observations were made during the implementation of the teaching and learning materials and the results showed that the teaching learning activities were consistent with the instructional implementation plans.  The implementation results showed that all of the students involved were able to meet the minimum competency standard prescribed by the school.  Students activities were dominated by pointing out  important conceps of the text  and asking questions. Most of the students gave positif respons to the instructional process.  So, it could be concluded the developed biology instruction materials for the pilot international standard junior high school students by implementing reciprocal teaching approach for the topic human breathing system were effective to achieve the prescribed competency.Penelitian ini bertujuan: 1) mengembangkan perangkat pembelajaran biologi SMP RSBI yang layak untuk digunakan dalam pembelajaran, dan 2) mendeskripsikan hasil penerapan perangkat pembelajaran biologi SMP RSBI.  Perangkat pembelajaran dikembangkan dengan  berorientasi pendekatan reciprocal teaching  pada materi sistem pernapasan manusia. Subyek penelitian adalah perangkat pembelajaran yang terdiri dari rencana pelaksanaan pembelajaran, buku ajar, lembar kegiatan siswa dan tes hasil belajar.  Subyek penelitian pada tahap ujicoba satu  adalah 12 siswa dan ujicoba dua adalah 23 siswa SMPN 1 Ngoro Mojokerto.  Penerapan perangkat pembelajaran pada saat ujicoba, menggunakan desain penelitian one group pretest-posttest design.  Hasil validasi menunjukkan bahwa perangkat pembelajaran yang dikembangkan adalah layak untuk  digunakan dalam pembelajaran. Tingkat kesulitan dan keterbacaan buku ajar dan lembar kegiatan siswa berkategori sedang dan tepat untuk pembelajaran. Hasil penerapan perangkat pembelajaran menunjukkan bahwa keterlaksanaan pembelajaran berkategori baik, aktivitas siswa selama pembelajaran didominasi oleh aktivitas menyampaikan konsep penting suatu bacaan dan mengajukan pertanyaan.  Hasil belajar siswa menunjukkan bahwa semua siswa tuntas pada ujicoba satu dan dua. Sebagian besar siswa  memberikan respon yang positif terhadap  pembelajaran. Disimpulkan bahwa pengembangan perangkat pembelajaran biologi SMP RSBI berorientasi pendekatan  reciprocal teaching pada materi sistem pernapasan manusia, efektif meningkatkan hasil belajar siswa.